applied anthropology and the inclusion of the Peruvian indian nation: 1940-1970 - Plasencia Soto, Rommel (2013)
The institucionalization of the Peruvian indigenism and its cancellation by reformist regime of Velasco is the scenario that this article exposes. While the agrarian reform of 1969 was one of the measures that claimed to the Peruvian indigenous population was also the time were paradoxically the term indian was replaced and the concept of «integration» used by nearly four decades he was overtaken by the socio-economic changes that happened.